PERPUSTAKAAN SEBAGAI CO-WORKING SPACE: MEMBANGUN KOMUNITAS PARA DIGITAL NOMAD - Muntashir, Muntashir (Publication Library and Information Science, 2022)
This article aims to review the concept of co-working space (Co-WS) as well as the principles of building and its influence in meeting the needs of a co-working space for digital nomads. In addition, this paper also discusses strategies for integrating Co-WS as a library service including the characteristics of librarians needed to manage Co-WS. This research is based on a literature survey in reviewing various matters related to the concept of Co-WS in general and related to the development of Co-WS in libraries. Co-WS as a library service aims to increase the social interaction of digital nomads who make libraries as a place to learn together, sharing knowledge, and collaborate so that networks are built between individuals and communities. The Co-WS space design must prioritize the values of openness, collaboration, accessibility, sustainability, and promote a community culture. The combination of physical and virtual space in the implementation of Co-WS services is the best strategy in helping social integration and learning to optimize the utilization of these services. Co-WS services are new opportunities and challenges for librarians who are required to be able to become community manager, as well as to become embedded business librarian in the development of an effective digital nomad community.